Intra-Regional Integration Among Selected OIC Countries: The Role Of Market Liberalization: Proceed. 2nd UMY-IIUM International Joint Seminar - Wisnu Wardhana, Nafiu Oladokun; dkk. (UMY & IIUM, 2009)
Intra-Regional Integration Among Selected OIC Countries: The Role Of Market Liberalization